Art and legitimacy: from the discourse to the ideological rhetoric - Queiroz, João Paulo (PORTO ARTE: Revista de Artes Visuais, 2017)
The circuits of artistic legitimacy have been modified and replaced by new agents. On one hand, the "relational aesthetics" and the decentering observed in "altermodernism" (Nicolas Bourriaud). On the other, the modernist role of the academies and their respective inertia of reaction to the avant-gardes have for decades yielded their place to a "Bologna paradigm" of lifelong learning, along with the strengthening of discursive skills, both for students and for teachers (the puzzle articulation between degrees, masters and doctorates). In the field of publics, their inclusion as a relational media has created new platforms of interaction and social institution, based on informal and more interactive formulas: the associations, the collectives, the young curators. This whole movement can be framed in the so-called "educational turn", that is characterized by focusing on the public and its creation - or education - using safeguard institutions (museums, educational services, foundations) or schools and art institutes (the lifelong formation of professional artists, or the new agents (cities, artistic residences, interventions in local power).